PARAMETRIC STUDY ON THE ROLE OF SUPPLEMENTARY MATERIALS IN MODULATING THE PERMEABILITY COEFFICIENT OF GEOPOLYMER CONCRETE - Amjad Ali; Shah Nawaz Khan Buledi; Baitullah Khan Kibzai; Muhammad Noor; Dr. M. Adil Khan; Muhammad Haris Javed (Spectrum of Engineering Sciences, 2025)
Geopolymer concrete represents an emerging trend within the concrete industry, serving as a potential alternative to traditional cement concrete. It offers numerous advantages compared to conventional cement-based materials. Geopolymer concrete is an environmentally friendly concrete composed of waste materials produced by thermal plants in various power generation industries. The alkaline activators in geopolymer concrete exhibit excellent heat resistance and strong adhesion between aggregates, leading to superior mechanical properties. Furthermore, geopolymer concrete exhibits significantly greater durability compared to conventional cement concrete. This study utilized marble waste and fly ash as raw materials for the production of geopolymer concrete. The materials were subjected to identical curing conditions to assess their mechanical properties. The investigation's results indicated that geopolymer concrete based on Marble can be produced under various curing conditions, demonstrating excellent physical and mechanical properties. The tests to evaluate the mechanical properties included split tensile, compressive, and water penetration assessments. The optimum mixes utilized in this research include 100% fly ash, 75% fly ash and 25% marble powder, 50% fly ash and 50% marble powder, and 25% fly ash and 75% marble powder. The alkaline activator to binder ratio is 0.40 [7]. The research focused on investigating geopolymer concrete's mechanical and physical properties.